Developments in the Curriculum and Teaching of Finance: Discussion - Walker, Charles F.; Meltzer, Allan H.; Peske, Edgar; Howard, Bion B.; Shelton, John P.; Naess, Ragnar D. (Journal of Finance, 1966)
Charles F. Walker, Allan H. Meltzer, Edgar Peske, Bion B. Howard, John P. Shelton, Ragnar D. Naess, Developments in the Curriculum and Teaching of Finance: Discussion, The Journal of Finance, Vol. 21, No. 2, Papers and Proceedings of the Twenty-Fourth Annual Meeting of the American Finance Association, New York, New York, December 28-30, 1965 (May, 1966), pp. 423-434